Faktor-Faktor Yang Berpengaruh Terhadap Likuiditas Bank Syariah - Muhammad Choirul Ichwan; Muhammad Nafik H.R (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This research aims to understand the influence of economic growth, rate of inflation, total funding, cost to income ratio, non performing financing, and financing to deposit ratio to liquidity of Islamic Bank. This Research uses a quantitative approach and a purposive sampling technique. The data used are collected through financial report of Islamic bank such as Muamalat Indonesia, BNI Syariah, BRI Syariah, Mandiri Syariah, and Mega Syariah period 2010-2014. Analysis of data is carried out by using the multiple linear regression analysis model. The result of this research is economic growth has significant to financing to deposit ratio.. This research suggests that to make the Bank not liquidity the Bank should increase the financing to deposit ratio.